Enkripsi Resep Dokter untuk Meminimalisir Penyalahgunaan Obat Menggunakan Algoritma AES Mode CBC - Agastya, Komang Wahyu; Eka Karyawati, Anak Agung Istri Ngurah (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 1 (2024): JNATIA Vol. 3, No. 1, November 2024DO - 10.24843/JNATIA.2024.v03.i01.p03, 2024)
Patient safety has always been a top priority, and medication error is a significant concern in this domain. Prescriptions are a crucial factor that can elevate the risk of medication errors. A study by Prof. Dr. Nurul Idrus involving 1,200 drug users revealed that a substantial number of respondents misused prescriptions and experimented with obtained medications to substitute for those they couldn't easily access. To address this issue and enhance patient safety, we propose utilizing the AES encryption algorithm to safeguard the confidentiality of prescriptions. AES encryption offers robust protection against unauthorized access and data breaches. Furthermore, employing the CBC (Cipher Block Chaining) mode provides an additional layer of security. In CBC mode, each block of the message is encrypted not only with the encryption key but also with the ciphertext of the previous block, resulting in a unique encrypted message even for identical plaintexts. This combination of AES encryption and CBC mode effectively safeguards prescription data, minimizing the potential for prescription misuse and medication errors, ultimately contributing to improved patient safety.